THE STATUS ON LABOUR MARKET OF THE ROMANIAN IMMIGRANTS FROM ITALY - Simionescu, Mihaela (Torun International Studies, 2020)
Knowing that Romanians represent the largest community of immigrants from Italy, the main aim of this paper is to study the status of these immigrants on the Italian labour market. Using statistical tests, random-effects ordered logistic regressions and generalized ridge regression model based on the survey data, the results showed significant differences between the number of males and females for Romanian immigrants in the period 2006-2018. Females have more chances than males to be active and to be employed on the Italian labour market due to their stability in services sector. Young people are more active and have more chances to be employed compared to old ones. The number of Romanian unemployed immigrants from Italy depends on tax rate, on low wage earners, adult participation in learning and harmonized index of consumer price.